A high-strength, high-toughness, high-corrosion-resistant magnesium alloy forging and preparation method thereof

By adding high solid solubility rare earth elements to the magnesium alloy, high precipitation reinforcement and solid solution reinforcement effects are achieved at room temperature, and a dense film structure is formed, which solves the problem of taking into account the strength and corrosion resistance of magnesium alloy, significantly improves its mechanical and corrosion resistance, and is suitable for applications in harsh environments.

CN119265440BActive Publication Date: 2025-03-28SHANGHAI JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411803432.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Existing magnesium alloys are difficult to maintain good corrosion resistance while increasing their strength, and their applications are limited in the fields of aerospace and marine engineering.

Method used

By adding rare earth elements with high solid solubility, such as gadolinium, yttrium, erbium, etc., the alloy can obtain high precipitation reinforcement and solid solution reinforcement effects at room temperature, and at the same time form a dense film layer structure, enhancing the density and protection of the magnesium oxide film and the corrosion product film.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of magnesium alloys, can maintain high strength and low corrosion rates under harsh environments, and is suitable for aerospace and marine ships and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265440B_ABST
    Figure CN119265440B_ABST
Patent Text Reader

Abstract

The present invention provides a high-strength, toughness and high-corrosion-resistant magnesium alloy forging and a preparation method thereof, and belongs to the technical field of magnesium alloys. The present invention uses materials such as magnesium-gadolinium master alloys, magnesium-erbium master alloys, and magnesium-zirconium master alloys, and adds other elements to enable the alloy to obtain high precipitation strengthening and solid solution strengthening effects at room temperature, significantly improving the mechanical properties of the alloy, and at the same time, by synergistically adding gadolinium, yttrium, erbium and lanthanum elements, promoting the densification of the corrosion film, achieving the improvement of the density and protection of the magnesium oxide film and the corrosion product film, and inhibiting the increase of microgalvanic corrosion caused by the precipitation of a large amount of second phases, thereby achieving the synergy of high strength and toughness and high corrosion resistance in magnesium alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnesium alloys, and in particular relates to a high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging and a preparation method thereof. Background Art

[0002] As the lightest metal structural material at present, magnesium alloy has a density of only 2 / 3 of aluminum and 1 / 4 of steel. It has many advantages such as high specific strength, easy processing and forming, good thermal and electrical conductivity, excellent shock absorption and electromagnetic shielding performance. Among them, magnesium alloys with high strength, toughness and corrosion resistance are in urgent need in the fields of aerospace, national defense, military industry, transportation, etc., and are of great significance to achieving structural lightweight and energy conservation and emission reduction. However, there is a problem of mutual exclusion between strength and corrosion resistance in magnesium alloys. The reason for the poor corrosion resistance of magnesium alloys is that magnesium has the lowest standard electrode potential (-2.37V / SHE) among structural metals. The second phase formed by alloying usually acts as a cathode to cause micro-galvanic corrosion with the magnesium matrix, while the magnesium matrix dissolves as an anode due to the low potential. On the other hand, the PBR (Pilling-Bedworth ratio) of the MgO oxide film on the surface of magnesium is only 0.81, which is less than 1, and it is impossible to form a densely covered oxide film. Therefore, its surface film is easily destroyed by chloride ions in the corrosive medium. The improvement of the strength of magnesium alloys usually requires precipitation strengthening by forming a large number of precipitated phases, and the presence of a large number of precipitated phases usually accelerates the microgalvanic corrosion of the magnesium matrix, resulting in a decrease in corrosion resistance. For example, the corrosion resistance of conventional magnesium alloys such as AZ91 and AZ80 magnesium alloys and other Mg-Al alloys is acceptable, but their toughness and high temperature performance are poor, making it difficult to meet the high strength and high corrosion resistance requirements in aerospace and marine shipbuilding. Although the VW114 (Mg-11Gd-4Y) alloy with a high rare earth content has high mechanical properties, the addition of a large number of rare earth elements leads to poor alloy casting process, and the casting process is prone to defects such as segregation and hot cracking. In addition, the addition of a large number of alloying elements leads to the formation of a large number of second phases, which seriously deteriorates the corrosion performance of the alloy, so it is difficult to use in the fields of aerospace and marine engineering. In addition, deformed magnesium alloys are usually extruded and rolled, and it is not easy to prepare large bulk deformed magnesium alloy materials. Large plastic deformation technology has unique advantages in improving the strength and toughness of magnesium alloys. Among them, multi-directional forging technology has the advantages of simple process and low cost. It can effectively refine grains and prepare large pieces of dense materials. It has broad application prospects in aerospace, transportation and marine engineering.

[0003] Chinese patent (publication number CN114351021A) discloses a high-performance cast magnesium alloy material for aerospace and a preparation method thereof. The cast magnesium alloy is composed of the following components by mass percentage: Gd: 5.5-8.5wt.%, Nd: 2.0-2.8wt.%, Zr: 0.4-0.6wt.%, Ag: 0-1.0wt.%. The alloy has high mechanical properties, strong fluidity, small shrinkage, shrinkage and hot cracking tendencies, and good overall casting processability. However, the addition of Ag element to the alloy will significantly reduce the corrosion resistance of the alloy. This is because the standard electrode potential of Ag is +0.8V / SHE, which is much higher than the standard electrode potential of Mg (-2.37 / SHE), and the solid solubility of Ag in magnesium is basically zero. It often exists in magnesium alloys in a single state, which will significantly accelerate the microgalvanic corrosion of the magnesium matrix as a high-potential impurity element. The above survey shows that the current high-performance magnesium alloys still have the problem of not being able to achieve both strength and corrosion resistance, which greatly limits the application of magnesium alloys in complex and harsh environments such as aerospace and ocean.

[0004] Therefore, there is an urgent need for a high-strength, high-toughness, high-corrosion-resistant magnesium alloy large forging to meet the current applications in the fields of aerospace and marine engineering. The present invention adds rare earth elements with high solid solubility to enable the alloy to obtain high precipitation strengthening and solid solution strengthening effects at room temperature, significantly improve the mechanical properties of the alloy, and at the same time form a dense film structure, increase the density and protection of the magnesium oxide film and the corrosion product film, and overcome the negative impact of the second phase on the corrosion performance. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength, tough and corrosion-resistant magnesium alloy forging and a preparation method thereof to meet the current demand for large-scale high-strength and corrosion-resistant magnesium alloy forgings in the fields of aerospace and marine engineering. By using materials such as magnesium-gadolinium master alloys, magnesium-erbium master alloys, and magnesium-zirconium master alloys, other elements are added to enable the alloy to obtain high precipitation strengthening and solid solution strengthening effects at room temperature, significantly improve the mechanical properties of the alloy, and at the same time form a dense film structure, increase the density and protection of the magnesium oxide film and the corrosion product film, and inhibit the adverse effects of the second phase on the corrosion performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A first aspect of the present invention provides a method for preparing a high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging, comprising the following steps:

[0008] Step S1: drying the pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy at 150-180° C. for 2-4 hours to remove moisture;

[0009] Step S2: Smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding the dried pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy described in step S1 into a crucible and melting them to obtain a magnesium alloy melt;

[0010] Step S3: Under the protective gas of carbon dioxide and sulfur hexafluoride, the magnesium alloy melt in step S2 is sequentially refined, stirred, and allowed to stand for heat preservation to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt;

[0011] Step S4: Under the protective gas of carbon dioxide and sulfur hexafluoride, the purified magnesium alloy melt in step S3 is subjected to semi-continuous casting, the mold is preheated in sequence, and the semi-continuous casting machine and the water cooling system are started to perform semi-continuous casting to produce magnesium alloy round bars with a diameter of 250-300 mm;

[0012] Step S5: cutting the magnesium alloy round rod in step S4 into alloy rods each having a length of 1000-1200 mm, and sequentially subjecting the alloy rods to turning, annealing, forging and aging heat treatment to obtain high-strength, high-toughness and high-corrosion-resistant magnesium alloy forgings;

[0013] Wherein, calculated by mass percentage, the high-strength, toughness and corrosion-resistant magnesium alloy forging includes 6-7wt% of gadolinium, 2-3wt% of yttrium, 0.5-1wt% of erbium, 0.1-0.2wt% of lanthanum, 0.05-0.5wt% of zirconium and the remainder of magnesium.

[0014] As a preferred solution, the preparation method of the magnesium-gadolinium master alloy comprises: adding 80-90 parts of magnesium particles by weight into a crucible, heating to 650-660° C. and keeping the temperature for 10-20 minutes under the protection of an argon atmosphere, then adding 10-20 parts of gadolinium powder, keeping the temperature at 740-745° C. for 30-35 minutes to obtain an alloy melt; subjecting the alloy melt to ultrasonic treatment to obtain a magnesium-gadolinium master alloy; the ultrasonic intensity of the ultrasonic treatment is 1.3-1.5 kW / cm 2 , the ultrasound time is 40~45min.

[0015] The addition of gadolinium to the magnesium-gadolinium master alloy refines the alloy grains and transforms the continuous network eutectic structure distributed along the grain boundaries into a semi-continuous network. At the same time, the magnesium-gadolinium master alloy is prepared by the melt matching method, using only magnesium and gadolinium elements, which can effectively reduce the impurity components of the magnesium-gadolinium master alloy, reduce the corrosion caused by impurities, and improve the corrosion resistance of the material.

[0016] As a preferred solution, the preparation method of the magnesium-erbium master alloy comprises: using a graphite crucible as an electrolytic cell, a graphite sheet as an anode, a pure magnesium block as a cathode, 80 to 100 parts by weight of sodium fluoride as a system electrolyte, and 30 to 40 parts by weight of erbium oxide as a raw material, and forming a magnesium-erbium master alloy at the cathode by electrolytic treatment; the electrolytic treatment comprises the following steps: adding sodium fluoride to the electrolytic cell, controlling the temperature to 1090 to 1100° C., to obtain a system electrolyte; adding erbium oxide and passing direct current, the current being 4200 to 4400A; electrolyzing for 60 to 70 minutes, taking out the cathode, and cooling to obtain the magnesium-erbium master alloy.

[0017] The erbium element in the magnesium-erbium master alloy has a grain refining effect on the alloy grains. At the same time, erbium can be concentrated at the grain boundaries, which can hinder the migration of grain boundaries and the growth of grains to a certain extent. Therefore, it can effectively improve the yield strength and tensile strength of magnesium alloy forgings.

[0018] As a preferred solution, the preparation method of the magnesium-zirconium master alloy comprises: weighing 200-300 parts of magnesium particles by weight, placing them in a reactor and heating them until they are melted, introducing carbon dioxide at a flow rate of 0.4-0.6 L / min, setting the reactor temperature to 800-850° C., adding 20-50 parts of zirconium chloride, and reacting for 1-2 hours; subjecting the product obtained by the reaction to ultrasonic treatment, and then blowing and refining it with argon gas, and finally casting it into a mold to obtain a magnesium-zirconium master alloy; the ultrasonic frequency of the ultrasonic treatment is 20-22 KHz, the power is 5-10 KW, and the treatment time is 10-20 minutes.

[0019] Adding zirconium to magnesium alloys can promote the formation of small and evenly distributed second-phase particles. These particles can refine the grains and promote heterogeneous nucleation, thereby significantly improving the mechanical properties of the alloy. In addition, the addition of zirconium can also help inhibit corrosion active points in the alloy. By reducing the number and activity of these points, the corrosion rate of the entire alloy material can be effectively reduced.

[0020] As a preferred solution, the volume ratio of carbon dioxide to sulfur hexafluoride in the protective gas is 1:(8-9).

[0021] As a preferred solution, the adding process in step S2 is: adding a pure magnesium block at 600-610°C, heating to 690-700°C to melt the pure magnesium block; then heating to 750-760°C, adding a magnesium-yttrium master alloy, a magnesium-lanthanum master alloy, a magnesium-gadolinium master alloy, and a magnesium-erbium master alloy; then heating to 780-785°C, adding a magnesium-zirconium master alloy, and keeping the temperature for 1-2 hours to obtain a magnesium alloy melt.

[0022] As a preferred solution, the refining treatment in step S3 is: adding a refining agent to the magnesium alloy melt, and then stirring for 10 to 20 minutes at a temperature of 750 to 760°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the static insulation treatment is: first standing at 740 to 750°C for 30 to 40 minutes, and then cooling to 700 to 710°C and standing for 20 to 30 minutes.

[0023] As a preferred solution, the semi-continuous casting temperature in step S4 is 690-700°C, and the mold preheating temperature is 180-200°C.

[0024] As a preferred solution, the annealing treatment temperature in step S5 is 450-480°C, and the treatment time is 20-24h; the forging treatment is: first, the magnesium alloy round bar is kept at 500-510°C for 20-24h, the forging die is preheated at 350-360°C for 1-2h, and then the magnesium alloy round bar is placed in the forging die, and mechanical forging treatment is performed at 400-420°C; the aging heat treatment temperature is 175-225°C, and the time is 24-48h;

[0025] The mechanical forging process is: the heated cast rod is transferred to the forging press gasket by a robot. The forging press is 3,000 tons, the forging head is rectangular, and the forging is multi-directional. The forging direction is adjusted by the robot. The X, Y, and Z directions are forged in sequence for 9 to 12 passes. The temperature during forging is 400 to 450°C.

[0026] A second aspect of the present invention provides a high-strength, toughness and corrosion-resistant magnesium alloy forging prepared by the preparation method described in the first aspect.

[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0028] 1. The present invention adds gadolinium, yttrium and erbium elements with high solid solubility. Since the elements have high solid solubility in magnesium, a large number of precipitation phases can be formed through aging treatment for precipitation strengthening, thereby significantly improving the mechanical properties of the alloy; the PBR (Pilling-Bedworth ratio) of the oxides of gadolinium, yttrium, erbium and lanthanum elements is greater than 1, which can significantly enhance the compactness of the MgO oxide film; gadolinium, yttrium, erbium and lanthanum have a standard electrode potential close to that of magnesium and will not significantly enhance the microgalvanic corrosion of the magnesium matrix; the addition of zirconium element can significantly refine the grains of the magnesium alloy and promote heterogeneous nucleation, thereby significantly improving the mechanical properties of the alloy; in addition, the addition of zirconium can react with impurities such as iron element, thereby significantly reducing the influence of impurity elements on the corrosion resistance of the magnesium alloy.

[0029] 2. The present invention uses multi-directional forging technology to continuously change the forging direction to continuously stretch and compress the material. Compared with unidirectional forging, it can effectively improve the problem of uneven core and edge structure during the forging process. At the same time, it can significantly affect the rheological stress during the material deformation process, and improve the anisotropy of the microstructure and mechanical properties. During the forging process, the coarse network second phase structure can be significantly damaged, and the grains can be significantly refined and the second phase distribution can be made more evenly dispersed, thereby significantly improving the mechanical properties and corrosion resistance of the alloy; in addition, the alloy of the present invention is formed by conventional casting and forging, and has the potential for low-cost large-scale application. The alloy strength and corrosion resistance are higher than the current traditional forged magnesium alloys. It is suitable for harsh environments such as aerospace and marine ships, and is suitable for the preparation of various shell materials.

[0030] 3. The present invention uses materials such as magnesium-gadolinium master alloy, magnesium-erbium master alloy, and magnesium-zirconium master alloy to prepare magnesium-gadolinium master alloy with low impurity content, which can significantly improve the corrosion resistance of the material; the erbium element in the magnesium-erbium master alloy has a grain refining effect on the alloy grains, which can effectively improve the yield strength and tensile strength of the magnesium alloy forgings; the zirconium in the magnesium-zirconium master alloy can promote the formation of small and evenly distributed second phase particles, which significantly improves the mechanical properties of the alloy, inhibits the corrosion active points in the alloy, and reduces the corrosion rate of the alloy material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a light microscope image of the microstructure of the magnesium alloy prepared in Example 1.

[0032] Figure 2 This is a corrosion cross-sectional morphology of the magnesium alloy in Example 1 after being immersed in a 3.5wt% NaCl solution for 7 days.

[0033] Figure 3 This is the corrosion cross-sectional morphology of commercial forged AZ80 magnesium alloy immersed in 3.5wt% NaCl solution for 7 days. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The sources of some components in the embodiments and comparative examples are as follows:

[0036] Pure magnesium block, CAS No. 7439-95-4, purchased from Shandong Ruifeng Metal Products Co., Ltd.;

[0037] Magnesium-yttrium master alloy, purity >99%, purchased from Hebei Qinbang New Materials Technology Co., Ltd.;

[0038] Magnesium-lanthanum master alloy, purity > 99%, purchased from Chongqing Yuhua New Materials Technology Co., Ltd.;

[0039] Potassium chloride, CAS No. 7447-40-7, purchased from Xilong Chemical Co., Ltd.;

[0040] Calcium chloride, CAS No. 10043-52-4, was purchased from Shanghai McLean Biochemical Technology Co., Ltd., China;

[0041] Barium chloride, CAS No. 10361-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] Calcium fluoride, CAS No. 7789-75-5, purchased from Shanghai Aladdin Co., Ltd.;

[0043] Yttrium chloride, CAS No. 10361-92-9, purchased from Shanghai Aladdin Co., Ltd.;

[0044] Graphite flakes, CAS No. 7782-42-5, were purchased from Shanghai Shanshan Technology Co., Ltd.;

[0045] Sodium fluoride, CAS No. 7681-49-4, purchased from Shandong West Asia Chemical Co., Ltd.;

[0046] Erbium oxide, CAS No. 12061-16-4, was purchased from Shanghai Hanlang New Material Technology Co., Ltd.;

[0047] Magnesium particles, CAS No. 7439-95-4, were purchased from Hebei Qinbang New Materials Technology Co., Ltd.;

[0048] Gadolinium powder, CAS No. 7440-54-2, was purchased from Shanghai Kelaman Reagent Co., Ltd.;

[0049] Zirconium chloride, CAS No. 10026-11-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0050] Commercial forged AZ80 alloy was purchased from Hunan Hengbo New Materials Co., Ltd.

[0051] Example 1

[0052] This embodiment provides a method for preparing a high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging, comprising the following steps:

[0053] Preparation of magnesium-gadolinium master alloy: 90 parts by weight of magnesium particles are added into a crucible, heated to 650°C for 20 minutes under argon atmosphere protection, and then 20 parts of gadolinium powder are added, and the mixture is kept at 740°C for 35 minutes to obtain an alloy melt; the alloy melt is subjected to ultrasonic treatment to obtain a magnesium-gadolinium master alloy; the ultrasonic intensity of the ultrasonic treatment is 11.5 kW / cm 2 , the ultrasonic time is 40min.

[0054] Preparation of magnesium-erbium master alloy: using a graphite crucible as an electrolytic cell, a graphite sheet as an anode, a pure magnesium block as a cathode, 100 parts by weight of sodium fluoride as a system electrolyte, 40 parts by weight of erbium oxide as a raw material, and forming a magnesium-erbium master alloy at the cathode through electrolytic treatment; the electrolytic treatment comprises the following steps: adding sodium fluoride to the electrolytic cell, controlling the temperature to 1100°C, obtaining a system electrolyte; adding erbium oxide and passing direct current, the current being 4400A; electrolyzing for 60 minutes, taking out the cathode, and cooling to obtain the magnesium-erbium master alloy.

[0055] Preparation of magnesium-zirconium master alloy: 300 parts of magnesium particles are weighed by weight, placed in a reactor and heated until melted, carbon dioxide is introduced at a flow rate of 0.6L / min, the reactor temperature is set to 850°C, 50 parts of zirconium chloride are added, and the reaction is carried out for 1 hour; the product obtained by the reaction is ultrasonically treated, then blown and refined with argon, and finally cast into a mold to obtain a magnesium-zirconium master alloy; the ultrasonic frequency of the ultrasonic treatment is 22KHz, the power is 10KW, and the treatment time is 10min.

[0056] Step S1: drying the pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy at 150° C. for 4 hours to remove moisture;

[0057] Step S2: Smelting is performed under the protective gas of carbon dioxide and sulfur hexafluoride, and the dried pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy described in step S1 are added into a crucible and melted. The specific adding process is: adding the pure magnesium block at 600° C., heating to 690° C. to melt the pure magnesium block; then heating to 750° C., adding the magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy and magnesium-erbium master alloy; then heating to 780° C., adding the magnesium-zirconium master alloy, and keeping the temperature for 2 hours to obtain a magnesium alloy melt.

[0058] Step S3: Under the protective gas of carbon dioxide and sulfur hexafluoride, the magnesium alloy melt in step S2 is successively refined, stirred, and allowed to stand and heat-insulate to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; the refining process is: adding a refining agent to the magnesium alloy melt, and then stirring for 10 minutes at a temperature of 750°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the standing and heat-insulating process is: first standing at 750°C for 30 minutes, and then cooling to 710°C and standing for 20 minutes.

[0059] Step S4: Under the protective gas of carbon dioxide and sulfur hexafluoride, the purified magnesium alloy melt in step S3 is subjected to semi-continuous casting treatment, the mold is preheated (the preheating temperature is 200° C.), and the semi-continuous casting machine and the water cooling system are started to perform semi-continuous casting (the casting temperature is 700° C.), so as to produce a magnesium alloy round bar with a diameter of 300 mm;

[0060] Step S5: cutting the magnesium alloy round rod in step S4 into alloy rods each having a length of 1200 mm, and sequentially subjecting the alloy rods to turning, annealing, forging and aging heat treatment to obtain high-strength, high-toughness and high-corrosion-resistant magnesium alloy forgings; the annealing temperature is 450°C, and the treatment time is 24 hours; the forging process is: first, the magnesium alloy round rod is kept at 500°C for 24 hours, the forging die is preheated at 350°C for 2 hours, and then the magnesium alloy round rod is placed in the forging die, and mechanical forging is performed at 420°C, and 9 forging passes are performed in a cycle along the X, Y, and Z directions, and the temperature during forging is 450°C; the temperature of the aging heat treatment is 200°C, and the time is 24 hours.

[0061] The volume ratio of carbon dioxide and sulfur hexafluoride in the protective gas is 1:9;

[0062] Wherein, calculated by mass percentage, the high-strength, toughness and corrosion-resistant magnesium alloy forging includes 6.93wt% of gadolinium, 2.89wt% of yttrium, 0.92wt% of erbium, 0.2wt% of lanthanum, 0.43wt% of zirconium and the remainder of magnesium.

[0063] Example 2

[0064] This embodiment provides a method for preparing a high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging, comprising the following steps:

[0065] Preparation of magnesium-gadolinium master alloy: 80 parts by weight of magnesium particles are added into a crucible, heated to 660°C for 10 minutes under argon atmosphere protection, and then 10 parts of gadolinium powder are added, and the mixture is kept at 740°C for 35 minutes to obtain an alloy melt; the alloy melt is subjected to ultrasonic treatment to obtain a magnesium-gadolinium master alloy; the ultrasonic intensity of the ultrasonic treatment is 1.3 kW / cm 2 , the ultrasonic time is 45min.

[0066] Preparation of magnesium-erbium master alloy: using a graphite crucible as an electrolytic cell, a graphite sheet as an anode, a pure magnesium block as a cathode, 80 parts by weight of sodium fluoride as a system electrolyte, and 30 parts by weight of erbium oxide as a raw material, and forming a magnesium-erbium master alloy at the cathode through electrolytic treatment; the electrolytic treatment comprises the following steps: adding sodium fluoride to the electrolytic cell, controlling the temperature to 1090° C., obtaining a system electrolyte; adding erbium oxide and passing direct current, the current being 4200A; electrolyzing for 70 minutes, taking out the cathode, and cooling to obtain the magnesium-erbium master alloy.

[0067] Preparation of magnesium-zirconium master alloy: 200 parts of magnesium particles are weighed by weight, placed in a reactor and heated until melted, carbon dioxide is introduced at a flow rate of 0.4L / min, the reactor temperature is set to 800°C, 20 parts of zirconium chloride are added, and the reaction is carried out for 2 hours; the product obtained by the reaction is ultrasonically treated, then blown and refined with argon, and finally cast into a mold to obtain a magnesium-zirconium master alloy; the ultrasonic frequency of the ultrasonic treatment is 20KHz, the power is 5KW, and the treatment time is 20min.

[0068] Step S1: drying the pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy at 180° C. for 2 h to remove moisture;

[0069] Step S2: Smelting is performed under the protective gas of carbon dioxide and sulfur hexafluoride, and the dried pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy described in step S1 are added into a crucible and melted. The specific adding process is: adding the pure magnesium block at 610° C., heating to 700° C. to melt the pure magnesium block; then heating to 760° C., adding the magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy and magnesium-erbium master alloy; then heating to 785° C. to add the magnesium-zirconium master alloy, and keeping the temperature for 1 hour to obtain a magnesium alloy melt.

[0070] Step S3: Under the protective gas of carbon dioxide and sulfur hexafluoride, the magnesium alloy melt of step S2 is successively refined, stirred, and allowed to stand and heat-insulate to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; the refining process is: adding a refining agent to the magnesium alloy melt, and then stirring for 10 minutes at a temperature of 760°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the standing and heat-insulating process is: first standing at 740°C for 40 minutes, and then cooling to 700°C and standing for 30 minutes.

[0071] Step S4: Under the protective gas of carbon dioxide and sulfur hexafluoride, the purified magnesium alloy melt in step S3 is subjected to semi-continuous casting, the mold is preheated (the preheating temperature is 180° C.), and the semi-continuous casting machine and the water cooling system are started to perform semi-continuous casting (the casting temperature is 690° C.), so as to produce a magnesium alloy round bar with a diameter of 300 mm;

[0072] Step S5: cutting the magnesium alloy round rod in step S4 into alloy rods each having a length of 1000 mm, and sequentially subjecting the alloy rods to turning, annealing, forging and aging heat treatment to obtain high-strength, high-toughness and high-corrosion-resistant magnesium alloy forgings; the annealing temperature is 480°C, and the treatment time is 20 hours; the forging process is: first, the magnesium alloy round rod is kept at 510°C for 20 hours, the forging die is preheated at 350°C for 2 hours, and then the magnesium alloy round rod is placed in the forging die, and mechanical forging is performed at 400°C, and 12 forging passes are performed in a cycle along the X, Y, and Z directions, and the temperature during forging is 400°C; the temperature of the aging heat treatment is 175°C, and the time is 48 hours.

[0073] The volume ratio of carbon dioxide and sulfur hexafluoride in the protective gas is 1:8;

[0074] Wherein, calculated by mass percentage, the high-strength, toughness and corrosion-resistant magnesium alloy forging includes 6.83wt% of gadolinium, 2.95wt% of yttrium, 1wt% of erbium, 0.2wt% of lanthanum, 0.5wt% of zirconium and the remainder of magnesium.

[0075] Example 3

[0076] This embodiment provides a method for preparing a high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging, comprising the following steps:

[0077] Preparation of magnesium-gadolinium master alloy: 85 parts by weight of magnesium particles are added into a crucible, heated to 655°C for 18 minutes under argon atmosphere protection, and then 16 parts of gadolinium powder are added, and the mixture is kept at 742°C for 33 minutes to obtain an alloy melt; the alloy melt is subjected to ultrasonic treatment to obtain a magnesium-gadolinium master alloy; the ultrasonic intensity of the ultrasonic treatment is 1.4 kW / cm 2 , the ultrasound time was 42 minutes.

[0078] Preparation of magnesium-erbium master alloy: using a graphite crucible as an electrolytic cell, a graphite sheet as an anode, a pure magnesium block as a cathode, 90 parts by weight of sodium fluoride as a system electrolyte, and 35 parts by weight of erbium oxide as a raw material, and forming a magnesium-erbium master alloy at the cathode through electrolytic treatment; the electrolytic treatment comprises the following steps: adding sodium fluoride to the electrolytic cell, controlling the temperature to 1095° C., obtaining a system electrolyte; adding erbium oxide and passing direct current, the current being 4300A; electrolyzing for 65 minutes, taking out the cathode, and cooling to obtain the magnesium-erbium master alloy.

[0079] Preparation of magnesium-zirconium master alloy: 280 parts of magnesium particles are weighed by weight, placed in a reactor and heated until melted, carbon dioxide is introduced at a flow rate of 0.5L / min, the reactor temperature is set to 820°C, 40 parts of zirconium chloride are added, and the reaction is carried out for 2 hours; the product obtained by the reaction is ultrasonically treated, then blown and refined with argon, and finally cast into a mold to obtain a magnesium-zirconium master alloy; the ultrasonic frequency of the ultrasonic treatment is 21KHz, the power is 8KW, and the treatment time is 18min.

[0080] Step S1: drying the pure magnesium block, the magnesium-yttrium master alloy, the magnesium-lanthanum master alloy, the magnesium-gadolinium master alloy, the magnesium-erbium master alloy and the magnesium-zirconium master alloy at 160° C. for 3 hours to remove moisture;

[0081] Step S2: Smelting is performed under the protective gas of carbon dioxide and sulfur hexafluoride, and the dried pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy described in step S1 are added into a crucible and melted. The specific adding process is: adding the pure magnesium block at 605° C., heating to 698° C. to melt the pure magnesium block; then heating to 755° C., adding the magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy and magnesium-erbium master alloy; then heating to 782° C., adding the magnesium-zirconium master alloy, and keeping the temperature for 2 hours to obtain a magnesium alloy melt.

[0082] Step S3: Under the protective gas of carbon dioxide and sulfur hexafluoride, the magnesium alloy melt in step S2 is successively refined, stirred, and allowed to stand and heat-insulate to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; the refining process is: adding a refining agent to the magnesium alloy melt, and then stirring for 15 minutes at a temperature of 755°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the standing and heat-insulating process is: first standing at 745°C for 36 minutes, and then cooling to 708°C for 25 minutes.

[0083] Step S4: Under the protective gas of carbon dioxide and sulfur hexafluoride, the purified magnesium alloy melt in step S3 is subjected to semi-continuous casting, the mold is preheated (the preheating temperature is 190° C.), and the semi-continuous casting machine and the water cooling system are started to perform semi-continuous casting (the casting temperature is 695° C.), so as to produce a magnesium alloy round bar with a diameter of 250 mm;

[0084] Step S5: cutting the magnesium alloy round rod in step S4 into alloy rods each having a length of 1200 mm, and sequentially subjecting the alloy rods to turning, annealing, forging and aging heat treatment to obtain high-strength, high-toughness and high-corrosion-resistant magnesium alloy forgings; the annealing temperature is 466°C, and the treatment time is 22 hours; the forging process is: first, the magnesium alloy round rod is kept at 505°C for 22 hours, the forging die is preheated at 355°C for 2 hours, and then the magnesium alloy round rod is placed in the forging die, and mechanical forging is performed at 410°C, and 9 forging passes are performed in a cycle along the X, Y, and Z directions, and the temperature during forging is 420°C; the temperature of the aging heat treatment is 225°C, and the time is 24 hours.

[0085] The volume ratio of carbon dioxide and sulfur hexafluoride in the protective gas is 1:9;

[0086] Wherein, calculated by mass percentage, the high-strength, toughness and corrosion-resistant magnesium alloy forging includes 6.1wt% of gadolinium, 2.06wt% of yttrium, 0.5wt% of erbium, 0.1wt% of lanthanum, 0.05wt% of zirconium and the remainder of magnesium.

[0087] Comparative Example 1

[0088] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-lanthanum master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy are added, and the rest is the same as Example 1.

[0089] Comparative Example 2

[0090] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy are added, and the rest is the same as Example 1.

[0091] Comparative Example 3

[0092] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-erbium master alloy and magnesium-zirconium master alloy are added, and the rest is the same as Example 1.

[0093] Comparative Example 4

[0094] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-gadolinium master alloy and magnesium-zirconium master alloy are added, and the rest is the same as Example 1.

[0095] Comparative Example 5

[0096] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-gadolinium master alloy and magnesium-erbium master alloy are added, and the rest is the same as Example 1.

[0097] Comparative Example 6

[0098] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-zirconium intermediate alloy is added, and the rest is the same as Example 1.

[0099] Comparative Example 7

[0100] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-erbium intermediate alloy is added, and the rest is the same as Example 1.

[0101] Comparative Example 8

[0102] This comparative example provides a method for preparing a high-strength, toughness and corrosion-resistant magnesium alloy forging. The difference between this comparative example and Example 1 is that no magnesium-gadolinium intermediate alloy is added, and the rest is the same as Example 1.

[0103] Comparative Example 9

[0104] This comparative example is a commercial forged AZ80 alloy purchased from Hunan Hengbo New Materials Co., Ltd.

[0105] Performance Testing

[0106] The magnesium alloy forgings prepared in the above examples and comparative examples were subjected to the following tests:

[0107] (1) Mechanical properties test

[0108] The mechanical properties test complies with the requirements of "GB / T 228.1-2021 Tensile test of metallic materials Part 1: Room temperature test method". The gauge size of the tensile sheet used for the test is 20×4×2mm, and three parallel test specimens are used.

[0109] (2) Corrosion performance test

[0110] The corrosion test solution is a neutral 3.5wt% NaCl solution, the test temperature is room temperature 25℃, the size of the test sample is 20×20×5mm, and the test time is 7 days. The immersion corrosion test complies with the requirements of the national standard "GB 10124-88 Metal Material Laboratory Uniform Corrosion Full Immersion Test Method", and the corrosion cleaning agent complies with the requirements of the national standard "GB∕T 16545-2015 Removal of Corrosion Products on Corrosion Test Specimens of Metals and Alloys". The weight loss rate is calculated by calculating the difference between the weight of the sample before the corrosion test and the weight of the sample after the corrosion test cleaning. Weight loss rate (mg / cm 2 / day) is equal to the weight difference divided by the surface area of ​​the sample divided by the number of test days; it can be converted into the average depth corrosion rate (mm / year) by conversion; the reduction of the solution in the burette is recorded by the hydrogen evolution test device to be equivalent to the volume of hydrogen gas released by magnesium corrosion, and the hydrogen evolution rate (mL / cm) is obtained by dividing the volume of hydrogen gas released by the surface area of ​​the sample divided by the number of test days. 2 / day).

[0111] The performance test results are shown in Table 1:

[0112] Table 1 Performance test results

[0113]

[0114] From the above performance test results, it can be seen that Examples 1-3 have high strength and ductility, showing strong toughness, yield strength of 305~326MPa, tensile strength of 412~438MPa, and elongation of 9.5%-10.2%. At the same time, they show excellent corrosion resistance, with a weight loss rate of 0.19~0.23mg / cm 2 / day, hydrogen evolution rate 0.28~0.37mL / cm 2 / day, corrosion rate 0.40~0.48mm / y; this is because it uses magnesium-gadolinium master alloy, magnesium-erbium master alloy, magnesium-zirconium master alloy and other materials, and adds other elements to enable the alloy to obtain high precipitation strengthening and solid solution strengthening effects at room temperature, significantly improving the mechanical properties of the alloy, while forming a dense film structure, increasing the corrosion resistance of magnesium alloy forgings. Figure 1 This is a light microscope image of the microstructure of Example 1, which has a uniform microstructure morphology. Figure 2From the corrosion cross-section morphology of Example 1 after immersion in 3.5wt% NaCl solution for 7 days, it can be seen that the alloy of the present invention has a uniform and dense corrosion product film, which indicates that the corrosion behavior of the alloy is ideal uniform corrosion. The dense corrosion product film is due to the synergistic addition of Gd, Y, Er and La elements, which promotes the densification of the corrosion product film.

[0115] However, since the comparative example did not adopt the necessary technical solution, it was significantly worse than the embodiment in the corresponding performance test. Compared with Example 1, the comparative example 1 did not add the magnesium-lanthanum master alloy, the magnesium-erbium master alloy and the magnesium-zirconium master alloy, so the yield strength and tensile strength decreased, and the weight loss rate, the hydrogen evolution rate and the corrosion rate increased; compared with Example 1, the comparative example 2 did not add the magnesium-gadolinium master alloy, the magnesium-erbium master alloy and the magnesium-zirconium master alloy, so the yield strength and tensile strength decreased, and the weight loss rate, the hydrogen evolution rate and the corrosion rate increased; compared with Example 1, the comparative example 3 did not add the magnesium-erbium master alloy and the magnesium-zirconium master alloy, so the yield strength and tensile strength decreased, and the weight loss rate, the hydrogen evolution rate and the corrosion rate increased. Compared with Example 1, Comparative Example 4 does not add magnesium-gadolinium master alloy and magnesium-zirconium master alloy, so the yield strength and tensile strength are reduced, and the weight loss rate, hydrogen evolution rate and corrosion rate are increased; Compared with Example 1, Comparative Example 5 does not add magnesium-gadolinium master alloy and magnesium-erbium master alloy, so the yield strength and tensile strength are reduced, and the weight loss rate, hydrogen evolution rate and corrosion rate are increased; Compared with Example 1, Comparative Example 6 does not add magnesium-zirconium master alloy, so the yield strength and tensile strength are reduced, and the weight loss rate, hydrogen evolution rate and corrosion rate are increased; Compared with Example 1, Comparative Example 7 does not add magnesium-erbium master alloy, so the yield strength and tensile strength are reduced; Compared with Example 1, Comparative Example 8 does not add magnesium-gadolinium master alloy, so the yield strength and tensile strength are reduced, and the weight loss rate, hydrogen evolution rate and corrosion rate are increased. In addition, it is compared with the commercial forged AZ80 alloy, and it can be found that the AZ80 alloy has low mechanical properties and poor corrosion resistance. Figure 3 This is a corrosion cross-section diagram of commercial forged AZ80 alloy after being immersed in a corrosive medium for 7 days. It can be seen that the protection of the corrosion product film of the traditional AZ80 alloy is poor, the corrosion product film is easy to crack and has low density, which leads to severe local corrosion of the alloy. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0116] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging, characterized in that: The following steps are involved: Step S1: drying the pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy at 150-180° C. for 2-4 hours to remove moisture; Step S2: Smelting under the protective gas of carbon dioxide and sulfur hexafluoride, adding the dried pure magnesium block, magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, magnesium-erbium master alloy and magnesium-zirconium master alloy described in step S1 into a crucible and melting them to obtain a magnesium alloy melt; Step S3: Under the protective gas of carbon dioxide and sulfur hexafluoride, the magnesium alloy melt in step S2 is sequentially refined, stirred, and allowed to stand for heat preservation to purify the melt and allow impurities to sink to the bottom of the crucible to obtain a purified magnesium alloy melt; Step S4: Under the protective gas of carbon dioxide and sulfur hexafluoride, the purified magnesium alloy melt in step S3 is subjected to semi-continuous casting, the mold is preheated in sequence, and the semi-continuous casting machine and the water cooling system are started to perform semi-continuous casting to produce magnesium alloy round bars with a diameter of 250-300 mm; Step S5: cutting the magnesium alloy round rod in step S4 into alloy rods each having a length of 1000-1200 mm, and sequentially subjecting the alloy rods to turning, annealing, forging and aging heat treatment to obtain high-strength, high-toughness and high-corrosion-resistant magnesium alloy forgings; Wherein, calculated by mass percentage, the high-strength, toughness and corrosion-resistant magnesium alloy forging includes 6-7wt% of gadolinium, 2-3wt% of yttrium, 0.5-1wt% of erbium, 0.1-0.2wt% of lanthanum, 0.05-0.5wt% of zirconium and the remainder of magnesium.

2. The preparation method according to claim 1, characterized in that: The preparation method of the magnesium-gadolinium master alloy comprises: adding 80-90 parts of magnesium particles by weight into a crucible, heating to 650-660° C. and keeping the temperature for 10-20 minutes under the protection of an argon atmosphere, then adding 10-20 parts of gadolinium powder, keeping the temperature at 740-745° C. for 30-35 minutes to obtain an alloy melt; subjecting the alloy melt to ultrasonic treatment to obtain a magnesium-gadolinium master alloy; the ultrasonic intensity of the ultrasonic treatment is 1.3-1.5 kW / cm 2 , the ultrasound time is 40~45min.

3. The preparation method according to claim 1, characterized in that: The preparation method of the magnesium-erbium master alloy comprises: using a graphite crucible as an electrolytic cell, a graphite sheet as an anode, a pure magnesium block as a cathode, 80-100 parts by weight of sodium fluoride as a system electrolyte, 30-40 parts by weight of erbium oxide as a raw material, and forming a magnesium-erbium master alloy at the cathode through electrolytic treatment; the electrolytic treatment comprises the following steps: adding sodium fluoride to the electrolytic cell, controlling the temperature to be 1090-1100° C., to obtain a system electrolyte; adding erbium oxide and passing direct current, the current being 4200-4400A; electrolyzing for 60-70 minutes, taking out the cathode, and cooling to obtain the magnesium-erbium master alloy.

4. The preparation method according to claim 1, characterized in that: The preparation method of the magnesium-zirconium master alloy comprises: weighing 200-300 parts of magnesium particles by weight, placing them in a reaction furnace and heating them until they are melted, introducing carbon dioxide at a flow rate of 0.4-0.6 L / min, setting the temperature of the reaction furnace to 800-850° C., adding 20-50 parts of zirconium chloride, and reacting for 1-2 hours; subjecting the reaction product to ultrasonic treatment, then blowing and refining it with argon gas, and finally casting it into a mold to obtain the magnesium-zirconium master alloy; the ultrasonic frequency of the ultrasonic treatment is 20-22 KHz, the power is 5-10 KW, and the treatment time is 10-20 minutes.

5. The preparation method according to claim 1, characterized in that: The volume ratio of carbon dioxide to sulfur hexafluoride in the protective gas is 1:(8-9).

6. The preparation method according to claim 1, characterized in that: The adding process of step S2 is: adding pure magnesium block at 600-610° C., heating to 690-700° C. to melt the pure magnesium block; then heating to 750-760° C., adding magnesium-yttrium master alloy, magnesium-lanthanum master alloy, magnesium-gadolinium master alloy, and magnesium-erbium master alloy; then heating to 780-785° C., adding magnesium-zirconium master alloy, and keeping warm for 1-2 hours to obtain a magnesium alloy melt.

7. The preparation method according to claim 1, characterized in that: The refining treatment in step S3 is as follows: adding a refining agent to the magnesium alloy melt, and then stirring for 10 to 20 minutes at a temperature of 750 to 760°C; the amount of the refining agent added is 1.5% of the total mass of the alloy, and the refining agent includes 49 parts of potassium chloride, 24 parts of calcium chloride, 14 parts of barium chloride, 6 parts of calcium fluoride and 3 parts of yttrium chloride by weight; the standing and heat preservation treatment is as follows: first standing at 740 to 750°C for 30 to 40 minutes, and then cooling to 700 to 710°C and standing for 20 to 30 minutes.

8. The preparation method according to claim 1, characterized in that: The semi-continuous casting temperature in step S4 is 690-700°C, and the mold preheating temperature is 180-200°C.

9. The preparation method according to claim 1, characterized in that: The annealing treatment temperature in step S5 is 450-480°C, and the treatment time is 20-24h; the forging treatment is: first, the magnesium alloy round bar is kept at 500-510°C for 20-24h, the forging die is preheated at 350-360°C for 1-2h, and then the magnesium alloy round bar is placed in the forging die, and mechanical forging treatment is performed at 400-420°C; the aging heat treatment temperature is 175-225°C, and the time is 24-48h; The mechanical forging process is as follows: the heated cast rod is transferred to the forging press gasket by a robot. The forging press is 3,000 tons, the forging head is rectangular, and multi-directional forging is performed. The forging direction is adjusted by the robot. The three directions of X, Y, and Z are forged in sequence for 9 to 12 passes. The temperature during forging is 400 to 450°C.

10. A high-strength, high-toughness and high-corrosion-resistant magnesium alloy forging, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-performance casting magnesium alloy material for aerospace and preparation method of high-performance casting magnesium alloy material

    CN114351021A

  • Low-cost and high-heat-strength wrought magnesium alloy and preparation method thereof

    CN103276264A

  • Preparation method of high strength microalloyed magnesium alloy ingot

    CN105385921A